2004
DOI: 10.1001/archpsyc.61.2.162
|View full text |Cite
|
Sign up to set email alerts
|

Increased Incidence of Diagnosed Depressive Illness in HypogonadalOlder Men

Abstract: Hypogonadal men showed an increased incidence of depressive illness and a shorter time to diagnosis of depression. Further prospective studies are needed to confirm these preliminary findings and to clarify the role of testosterone in the treatment of depressive illness in older men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
109
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(121 citation statements)
references
References 38 publications
10
109
2
Order By: Relevance
“…The trend toward higher opioid dosage for hypogonadal patients is consistent with previous reports, 45 including our own, 44,49 of hypogonadism among cancer survivors without evidence of recurrent disease who use opioid therapy for chronic pain. Our patients with autonomic dysfunction did not seem to have a greater frequency of fatigue or, indeed, of any major symptoms except for dyspnea.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The trend toward higher opioid dosage for hypogonadal patients is consistent with previous reports, 45 including our own, 44,49 of hypogonadism among cancer survivors without evidence of recurrent disease who use opioid therapy for chronic pain. Our patients with autonomic dysfunction did not seem to have a greater frequency of fatigue or, indeed, of any major symptoms except for dyspnea.…”
Section: Discussionsupporting
confidence: 91%
“…28,29 The finding of a strong association between hypogonadism and negative mood, as documented by the HADS-A, HADS-D, and FACT Emotional Well-Being subscale, is consistent with the reported impact of hypogonadism on mood in elderly men, 45 in individuals with HIV wasting, 41 or in patients with ischemic heart disease. 46 Patients undergoing therapeutic elimination of testosterone, mainly for prostate carcinoma, often experience negative mood changes, including depression and anxiety.…”
Section: Discussionsupporting
confidence: 79%
“…One study has found that men with hypogonadal testosterone values are at higher risk of developing depression, 10 while others have not. 5,11 In this paper, we examine the correlation between depression symptoms and hypogonadsim in men attending an ED clinic.…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective study by Shores et al, hypogonadal men over 45 years of age had a 3.5-fold risk increase in the incidence of depression when compared to eugonadal men. 23 It has been found that cerebral perfusion itself maybe altered in hypogonadism. Testosterone replacement in hypogonadal men has been shown to increase blood flow to the midbrain, superior frontal gyrus, and midcingulate gyrus.…”
Section: Discussionmentioning
confidence: 99%